A Review on Synthetic Thiazole Derivatives as an Antimalarial Agent - Kalita, Tutumoni; Choudhury, Ankita; Shakya, Anshul; Ghosh, Surajit K.; Singh, Udaya Pratap; Bhat, Hans Raj (Current Drug Discovery Technologies, 2024)
Background: Thiazole is a widely studied core structure in heterocyclic chemistry and has proven to be a valuable scaffold in medicinal chemistry. The presence of thiazole in both naturally occurring and synthetic pharmacologically active compounds demonstrates the adaptability of these derivatives. Methods: The current study attempted to review and compile the contributions of numerous researchers over the last 20 years to the medicinal importance of these scaffolds, with a primary focus on antimalarial activity. The review is based on an extensive search of PubMed, Google Scholar, Elsevier, and other renowned journal sites for a thorough literature survey involving various research and review articles. Results: A comprehensive review of the antimalarial activity of the thiazole scaffold revealed potential therapeutic targets in Plasmodium species. Furthermore, the correlation of structure-activity-relationship (SAR) studies from various articles suggests that the thiazole ring has therapeutic potential. Conclusion: This article intends to point researchers in the right direction for developing potential thiazole-based compounds as antimalarial agents in the future.
Keywords: Thiazole derivatives